Pengaruh Penggunaan Beberapa Paket Teknologi terhadap Perkembangan Penyakit Layu Fusarium pada Tanaman Cabai Rawit (Capsicum frutescens L.) dan Cabai Besar (Capsicum annuum L.) di Dataran Tinggi - RUSMAN, I WAYAN; SUNITI, NI WAYAN; SUMIARTHA, I KETUT; SUDIARTA, I PUTU; WIRYA, GUSTI NGURAH ALIT SUSANTA; UTAMA, I MADE SUPARTHA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Influence of Some Packages of Technology to Fusarium Wilt Disease Development on Cayenne Chili Plants (Capsicum frutescens L.) and Long Chili (Capsicum annuum L.) in the Highlands The research was conducted in order to determine the influence and effectiveness of some technologies of Trichoderma sp. compost, rain shelter and pesticides to control the development of fusarium wilt disease on long chili and cayenne chili plants in the highlands. This research was done from September 2017 to February 2018, taking place in Pancasari Village, Buleleng Regency and in the Laboratory of Plant Disease, Udayana University. The study used a Factorial Randomized Block Design with two factors and replicated four times. The first factor was chili type, long chili and cayenne chili. The second factor was the use of technologies, Trichoderma sp. compost, rain shelter and pesticide. The variables observed in this research were symptoms and percentage of fusarium wilt disease. The results showed that all treatment technologies effectively suppressed disease development when compared to control treatment. Percentages of damage by fusarium wilt disease on Trichoderma sp., rain shelter, pesticide and control treatment were 22.50%, 23.75%, 27.50% and 45.00%, respectively.